Genetic Basis of Sexual Maturation Heterosis: Insights From Ovary lncRNA and mRNA Repertoire in Chicken - Wang, Yuanmei; Yuan, Jingwei; Sun, Yanyan; Li, Yunlei; Wang, Panlin; Shi, Lei; Ni, Aixin; Zong, Yunhe; Zhao, Jinmeng; Bian, Shixiong; Ma, Hui; Chen, Jilan (Frontiers in Endocrinology, 2022)
Sexual maturation is fundamental to the reproduction and production performance, heterosis of which has been widely used in animal crossbreeding. However, the underlying mechanism have long remained elusive, despite its profound biological and agricultural significance. In the current study, the reciprocal crossing between White Leghorns and Beijing You chickens were performed to measure the sexual maturation heterosis, and the ovary lncRNAs and mRNAs of purebreds and crossbreeds were profiled to illustrate molecular mechanism of heterosis. Heterosis larger than 20% was found for pubic space and oviduct length, whereas age at first egg showed negative heterosis in both crossbreeds. We identified 1170 known lncRNAs and 1994 putative lncRNAs in chicken ovary using a stringent pipeline. Gene expression pattern showed that nonadditivity was predominant, and the proportion of nonadditive lncRNAs and genes was similar between two crossbreeds, ranging from 44.24% to 49.15%. A total of 200 lncRNAs and 682 genes were shared by two crossbreeds, respectively. GO and KEGG analysis showed that the common genes were significantly enriched in the cell cycle, animal organ development, gonad development, ECM-receptor interaction, calcium signaling pathway and GnRH signaling pathway. Weighted gene co-expression network analysis (WGCNA) identified that 7 out of 20 co-expressed lncRNA-mRNA modules significantly correlated with oviduct length and pubic space. Interestingly, genes harbored in seven modules were also enriched in the similar biological process and pathways, in which nonadditive lncRNAs, such as MSTRG.17017.1 and MSTRG.6475.20, were strongly associated with nonadditive genes, such as CACNA1C and TGFB1 to affect gonad development and GnRH signaling pathway, respectively. Moreover, the results of real-time quantitative PCR (RT-qPCR) correlated well with the transcriptome data. Integrated with positive heterosis of serum GnRH and melatonin content detected in crossbreds, we speculated that nonadditive genes involved in the GnRH signaling pathway elevated the gonad development, leading to the sexual maturation heterosis. We characterized a systematic landscape of ovary lncRNAs and mRNAs related to sexual maturation heterosis in chicken. The quantitative exploration of hybrid transcriptome changes lays foundation for genetic improvement of sexual maturation traits and provides insights into endocrine control of sexual maturation.